1986
DOI: 10.18174/njas.v34i1.16814
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter production and nitrogen utilization in cropping systems with grass, lucerne and maize. 2. Nitrogen yield and utilization.

Abstract: The N yield and the N use efficiency were studied in a 3-year experiment with various cropping systems of Lolium perenne, Medicago sativa and maize. N yields of L. perenne and maize were about 450 and 200 kg/ha, resp. N yields of M. sativa ranged from about 400 to 600 kg/ha depending on crop age and weather conditions. N fixation rates of M. sativa were assessed in 1982 and ranged from 107 to 507 kg/ha for high (450 kg N/ha) and no N fertilization, resp. The after-effects of 1-, 2- and 3-year crops of L. peren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It was found that above-ground DM yields ranged from 13.4 to 19.8, from 13.4 to 18.1 and from 13.7 to 17.1 t ha −1 for grass, lucerne and maize, respectively (DM: dry matter). The associated N yields ranged from 413 to 452, from 392 to 577 and from 188 to 220 kg ha −1 (Spiertz and Sibma, 1986). Grass showed the highest productivity in the first year and lucerne in the last year.…”
Section: Arable Cropping Systemsmentioning
confidence: 99%
“…It was found that above-ground DM yields ranged from 13.4 to 19.8, from 13.4 to 18.1 and from 13.7 to 17.1 t ha −1 for grass, lucerne and maize, respectively (DM: dry matter). The associated N yields ranged from 413 to 452, from 392 to 577 and from 188 to 220 kg ha −1 (Spiertz and Sibma, 1986). Grass showed the highest productivity in the first year and lucerne in the last year.…”
Section: Arable Cropping Systemsmentioning
confidence: 99%
“…The presentation of the data is restricted to grass and maize with the highest nitrogen dressings and lucerne without nitrogen dressing. More data on the yield response to nitrogen are presented elsewhere (Spiertz & Sibma, 1986). Significances for total DM ha" 1 year" 1 : 1980: L3 < G3 1981: L2 < (G2 + G3)/2; L3=(G2 + G3)/2; L3=L2; L3=G3 1982: L1=L2=L3 > Gl > G2=G3 > or < = significant at 95% level; = = not significant at 95% level.…”
Section: Growth Patterns Of Grass and Lucernementioning
confidence: 99%
“…This paper deals with growth, forage yield and quality, distribu tion of dry matter, root/shoot-ratio, leaf characteristics and light interception. The data on nitrogen yield and nitrogen fixation will be presented and discussed in a sec ond paper (Sibma & Spiertz, 1986); that paper also includes the residual effects of the various cropping systems on the dry matter and nitrogen yield of the following crop maize.…”
Section: Introductionmentioning
confidence: 99%